Is the quantitative cut-off a suitable surrogate to ensure a good indoor air quality regarding the mycobiota in health care facilities? - Viegas, Carla (2019)
Projeto EXPOsE – Establishing protocols to assess occupational exposure to microbiota in clinical settings (02/SAICT/2016 – Project nº 23222).